Pathway to Sustainability: An Overview of Renewable Energy Integration in Building Systems - Reddy, Vennapusa Jagadeeswara; Hariram, N. P.; Mohd Fairusham, Ghazali; Kumaramasy, Sudhakar (MDPI, 2024)
Decarbonizing the building sector is crucial for mitigating climate change, reducing carbon emissions, and achieving an energy production–consumption balance. This research aims to identify key design principles and strategies to enhance energy savings and analyze the integration potential of renewable energy sources (RES) such as solar, wind, geothermal, and biomass, providing in-depth technical exploration and evaluating current building developments. Moreover, the study also examines recent developments, explicitly focusing on integrating hybrid renewable energy systems, energy storage solutions, and AI-based technological innovations. Through comprehensive analysis and critical evaluation, this research provides valuable insights and practical recommendations for achieving building sustainability and advancing the transition towards a low-carbon built environment.